Nomenclatural changes, new country records and range extensions of Baridinae (Coleoptera, Curculionidae) from China - Prena, Jens; Yang, Jiani; Ren, Li; Wang, Zhiliang; Liu, Ning; Zhang, Runzhi (Zootaxa, 2014)
Thirteen relatively frequently collected species of baridine weevils from mainland China were mapped to improve our understanding of biogeographic patterns and distributional ranges of Baridinae in the Palaearctic and Oriental regions. This simple case study showed that taxonomists tend to underestimate the spatial scope required in regional investigations and descriptive works often resulting in widespread species being described numerous times. Several apparently uncommon species with uncertain relationships, known previously only from moderately high latitudes in the Palaearctic region, showed Oriental affinities. In each region, species may occur over many thousands of kilometers not only in East-West but also in North-South directions. New synonyms are Mimophilus Faust (=Baridiomorphus Voss), Acythopeus inflatirostris Voss (=Acythopeus proximus Voss), Baris albisquama Zaslavskij (=Baris ljaodunensis Zaslavskij), Mimophilus tragicus Faust (=Baridiomorphus conicollis Voss), Moreobaris deplanata (Roelofs) (=Acythopeus patruelis Voss), Baris pilosa Roelofs (=Baris blennus Marshall, =Baris piliventris Zaslavskij, =Baris pygidialis Voss, =Baris suvorovi Reitter), Baris artemisiae (Panzer) (=Baris corvina Voss), Pellobaris melancholica (Roelofs) (=Paracythopeus collaris Voss), Pteridobaris maritima (Roelofs) (=Baris quinquecarinata Zaslavskij) and Ulobaris kuchenbeisseri Hartmann (=Baris pseudospitzyi Zaslavskij, =Baris ussuriensis ussuriensis Zaslavskij, =Baris ussuriensis chinganensis Zaslavskij). New combinations are Athesapeuta gracilis (Voss) (from Eumycterus Schönherr), Athesapeuta inornata (Voss) (from Baris Germar) and Nespilobaris inflatirostris (Voss) (from Acythopeus Pascoe). Baridius vestitus Perris (not Boheman) and Baris pygidialis Hustache (not Voss) are newly recognized primary homonyms. A lectotype is designated for Moreobaris deplanata. Twenty-four species are recorded newly from China.